2022
DOI: 10.1017/jfm.2022.539
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bifurcated dual vortex streets in the wake of an oscillating foil

Abstract: Wake evolution of an oscillating foil with combined heaving and pitching motion is evaluated numerically for a range of phase offsets ( $\phi$ ), chord-based Strouhal numbers ( $St_c$ ) and Reynolds numbers ( $Re$ ). The increase in $\phi$ from $90^\circ$ to $180^\circ$ at a given $St_c$ and $Re$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…This further coincides with a decrease in trailing edge amplitude as described by. 15,22 We also observe that the range of f* between 0.24 and 0.40 shows a delayed wake transition from 2P+2S to 2P within heave-dominated regime compared to the pitch-dominated regime at ϕ<180, for example. This could again be an implication of weak or no interaction (and merging) near the trailing edge of the foil due to lower strength of generated vorticity.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…This further coincides with a decrease in trailing edge amplitude as described by. 15,22 We also observe that the range of f* between 0.24 and 0.40 shows a delayed wake transition from 2P+2S to 2P within heave-dominated regime compared to the pitch-dominated regime at ϕ<180, for example. This could again be an implication of weak or no interaction (and merging) near the trailing edge of the foil due to lower strength of generated vorticity.…”
Section: Resultsmentioning
confidence: 59%
“…The reduction of trailing edge amplitude within the heave-dominated regime corresponds to decreasing relative vorticity generated at the trailing edge compared to the leading edge. 22 This characteristic feature thus yields a paired configuration of leading and trailing edge vortical structures, even at high f* for the heave-dominated kinematics, thereby explaining the 2P mode configuration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The relevant studies are the prime motivators for the new technology in this regard, such as marine, aerial, and energy territory [ 64 ]. Using numerical methods to simulate and analyze relevant experimental conditions, such as wake state, has become an effective research method at present [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…When Re = 1000, 2000, we found that at the vertical line of the wake with the same horizontal position, vortex eyes appeared two to three times. This unstable vortex shedding is a common phenomenon and can be simulated by improving the model to realize the dual Karman vortex street [ 65 ].…”
Section: Resultsmentioning
confidence: 99%